Sfericase protease, phytase, and xylanase combination improves body weight, feed conversion rate, ileal digestibility, and gut morphology in broilers - Rodríguez-Soriano, Froylán A.; López-Coello, Carlos; Ávila-González, Ernesto; Arce-Menocal, José; Fascina, Vitor Barbosa; Chárraga-Aguilar, Silvestre (Frontiers in Animal Science, 2025)
IntroductionThis study aimed to evaluate the effects of a novel sfericase protease—an endopeptidase from the serine protease family, subtilisin subfamily A (MEROPS ID S08.113)—combined with phytase and xylanase on broiler performance, gut morphology, litter quality, and ileal digestibility.MethodsA total of 1,800 Cobb 500 male chickens were randomly allocated into 36 pens with four dietary treatments and nine replicates per treatment (50 birds per replicate) until 42 days of age. The treatments included: (1) a positive control (PC) following adapted Cobb nutritional recommendations; (2) a negative control (NC) with crude protein and amino acid reductions (0.500% crude protein, 0.041% digestible lysine, 0.040% digestible methionine + cysteine, 0.049% digestible threonine, and 0.032% digestible arginine) compared to PC; (3) NC supplemented with 10,000 new feed protease units (NFP)/kg feed; and (4) NC supplemented with 30,000 NFP/kg feed. Diets, provided in mash form, consisted of corn, soybean meal, canola meal, distiller’s dried grains with solubles, meat and bone meal, corn gluten meal, and soybean oil.ResultsAt 42 days of age, broilers fed the NC diet had significantly lower body weight than those in the PC and protease-supplemented groups (p < 0.05). Feed conversion ratio (FCR) was poorest in the NC group, significantly differing from PC and NC + 10,000 NFP/kg (p < 0.05). Gut morphology analysis revealed significant differences in villus length and number, crypt depth, and surface area among treatments (p < 0.05), with the NC exhibiting the lowest surface area per μm². Energy digestibility was lowest in the PC group, whereas protease-supplemented groups (NC + 10,000 and 30,000 NFP/kg) had the highest digestibility values (p < 0.05). Improvements in energy and nitrogen digestibility correlated significantly with body weight, FCR, and gut morphology (p < 0.05).DiscussionThese findings demonstrate that the inclusion of sfericase protease, in combination with phytase and xylanase, positively influences broiler performance, gut morphology, and nutrient digestibility. Optimizing enzyme inclusion based on diet composition and ingredient quality provides practical benefits in commercial broiler production.